1984
DOI: 10.1042/bj2220535
|View full text |Cite
|
Sign up to set email alerts
|

A transient increase in diacylglycerols is associated with the action of vasopressin on hepatocytes

Abstract: Vasopressin induced a transient increase of 50% in the total concentration of diacylglycerols (determined by g.l.c.) in isolated hepatocytes. The increase was maximal at 0.25 min, and the concentration of diacylglycerols in cells treated with vasopressin had returned to the basal value by 4 min. No change in the concentration of diacylglycerols was observed after the treatment of cells with glucagon. The dependency of this effect on the concentration of vasopressin was similar to that of the effect of the horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
24
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 45 publications
5
24
0
Order By: Relevance
“…A. Spitzer, unpublished work). (2) The accumulation of total DAG was sustained up to the last time analysed (10 min), a finding similar to that previously obtained for control cells [29][30][31][32] and at variance with the transient increase reported by others [33,34]. (3) The release of C18 0-and C20:4-DAG was detected before other DAG acyl groups.…”
Section: Discussionsupporting
confidence: 72%
“…A. Spitzer, unpublished work). (2) The accumulation of total DAG was sustained up to the last time analysed (10 min), a finding similar to that previously obtained for control cells [29][30][31][32] and at variance with the transient increase reported by others [33,34]. (3) The release of C18 0-and C20:4-DAG was detected before other DAG acyl groups.…”
Section: Discussionsupporting
confidence: 72%
“…In vasopressin stimulated hepatocytes one laboratory reported enrichement in both stearic and arachidonic acid after 1 min of exposure to the agonist (21), while another found increases in stearic and less changes in arachidonic acid content (22). However the smaller increase ofarachidonic acid could have been due to oxidation ofthis labile fatty acid during the HPLC purification.…”
Section: Discussionmentioning
confidence: 99%
“…A rapid and usually transient accumulation of DG associated with stimulated phosphoinositide breakdown has been demonstrated in platelets [21,63,116,146,148,204,236,254], pancreas [18,67], mast cells [144], 3T3 cells [108], pituitary cells [74,198,249], GH3 cells [75], and liver [142,302]. A rapid and usually transient accumulation of DG associated with stimulated phosphoinositide breakdown has been demonstrated in platelets [21,63,116,146,148,204,236,254], pancreas [18,67], mast cells [144], 3T3 cells [108], pituitary cells [74,198,249], GH3 cells [75], and liver [142,302].…”
Section: Diacylglyeerolmentioning
confidence: 99%
“…A rapid and usually transient accumulation of DG associated with stimulated phosphoinositide breakdown has been demonstrated in platelets [21,63,116,146,148,204,236,254], pancreas [18,67], mast cells [144], 3T3 cells [108], pituitary cells [74,198,249], GH3 cells [75], and liver [142,302]. Some studies [18,142] have suggested that only a part of this newly generated DG is due to phosphoinositide breakdown, and the rest is considered to arise from other lipids. Some studies [18,142] have suggested that only a part of this newly generated DG is due to phosphoinositide breakdown, and the rest is considered to arise from other lipids.…”
Section: Diacylglyeerolmentioning
confidence: 99%